2018
DOI: 10.1051/matecconf/201822501013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diesel-Biodiesel Blends in Diesel Engine Single Cylinder on the Emission Characteristic

Abstract: Biodiesel is an alternative fuel that is used in a diesel engine as a substitute for diesel fuel. However, using biodiesel without a modified engine can cause higher NOx emissions. Therefore, to reduce harmful emissions some strategy must be proposed or or a change in the injection is performed. In this study, injection schemes and engine performance injection time, emissions and firing characteristics of biodiesel mixing results in engines were investigated by using GT-POWER simulation. The simulations in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Here, we show that leucine auxotrophy imposes a strong effect on fermentation phenotypes, and specifically aroma formation, because metabolism of leucine in yeast is tightly linked to the formation of various flavor-active compounds [ 53 ], including organic acids, aldehydes, and higher (fusel) alcohols [ 54 ]. Several of these higher alcohols are currently explored as biofuels [ 55 ], but they are also the main precursors of acetate esters, which are important contributors to the flavor and aroma of alcoholic beverages [ 56 , 57 ]. In particular, LEU2 encodes for beta-isopropylmalate dehydrogenase, involving in the conversion of α-ketoisovalerate (KIV) to α-ketoisocaproate (KIC) which is a direct intermediate in the biosynthetic pathway of isoamyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that leucine auxotrophy imposes a strong effect on fermentation phenotypes, and specifically aroma formation, because metabolism of leucine in yeast is tightly linked to the formation of various flavor-active compounds [ 53 ], including organic acids, aldehydes, and higher (fusel) alcohols [ 54 ]. Several of these higher alcohols are currently explored as biofuels [ 55 ], but they are also the main precursors of acetate esters, which are important contributors to the flavor and aroma of alcoholic beverages [ 56 , 57 ]. In particular, LEU2 encodes for beta-isopropylmalate dehydrogenase, involving in the conversion of α-ketoisovalerate (KIV) to α-ketoisocaproate (KIC) which is a direct intermediate in the biosynthetic pathway of isoamyl alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…However, the thermal efficiency of the brakes (BTE) for all trials conducted showed a decrease. The use of alternative fuels for diesel engines has also been carried out by several previous researchers [15][16][17][18][19][20][21][22][23]. Alternative fuels for diesel engines have shown excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best alternatives is the development of biofuels such as biodiesel, which can be used in internal combustion engines without the need to modify them, thus reducing environmental pollution; in addition, they are sustainable and economical in nature, unlike conventional fuels [4]. Biodiesel is the most widely used biofuel and is produced from vegetable oils such as soybeans, cotton seeds, sunflower, and palm oil [5]. It shows better characteristics in ignition quality, lack of sulfur and aromatic content, renewal capacity, and biodegradability, and 30 % to 71 % reduction in emissions of polluting gases [6], in addition, to providing less engine wear, lower oil consumption and better thermal efficiency compared to that of traditional diesel fuel [7].…”
Section: Introductionmentioning
confidence: 99%